Cause of The Low Positivity of Blood Culture in Septic Patients - Krishna Yana; Bachti Alisjahbana; Yovita Hartantri (Jurnal Penyakit Dalam Indonesia)
Introduction. Sepsis due to bacterial infection is one of the main causes of high disease morbidity and mortality. Management of sepsis, the detection of bacteriemia by examination of blood cultures has an important role, but until now the positivity of blood culture results at Hasan Sadikin Hospital (RSHS) is still low (13.45%). The purpose of this study was to determine profile the causes of low positivity of blood culture results in sepsis patients in RSHS.